2019
DOI: 10.6023/a19060241
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Assembly of Chiral Structure of Diphenylalanine Peptide

Abstract: Chirality is ubiquitous in nature and it plays an important role in both biological and material sciences. Inspired by nature, scientists have prepared various chiral structures or hybrid materials by self-assembly of polypeptides, amino acids, carbohydrates and their derivatives. These studies provide a good model for understanding of supramolecular chirality and mimicking the self-assembly of organisms. In the past decade, diphenylalanine (FF) and its derivatives have attracted great attentions and have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…The subjects monitored in this study were derived from ethnic minority autonomous counties and analyzed in three groups of Li, Han, and other ethnic minorities (mainly including Miao, Zhuang, and Yao). It revealed that the prevalences of undernutrition and wasting were greater among Li than Han in 8 years (except for 2020), which is consistent with Wang Zeyuan’s [ 30 ] findings and suggested this may be due to the genetic, dietary patterns, lifestyle, economic, and cultural level variables [ 31 , 32 ].Scholars have analyzed the body composition and shape of the Li and discovered that they are thinner and have more developed muscles than Han [ 33 ].…”
Section: Discussionsupporting
confidence: 75%
“…The subjects monitored in this study were derived from ethnic minority autonomous counties and analyzed in three groups of Li, Han, and other ethnic minorities (mainly including Miao, Zhuang, and Yao). It revealed that the prevalences of undernutrition and wasting were greater among Li than Han in 8 years (except for 2020), which is consistent with Wang Zeyuan’s [ 30 ] findings and suggested this may be due to the genetic, dietary patterns, lifestyle, economic, and cultural level variables [ 31 , 32 ].Scholars have analyzed the body composition and shape of the Li and discovered that they are thinner and have more developed muscles than Han [ 33 ].…”
Section: Discussionsupporting
confidence: 75%
“…Consequently, the electrolysis of methanol on the surface of Pt electrode and the condensation of produced HCHO on the electrode with methanol in the solution are both enhanced by the ionic liquid EmimBF 4 as electrolyte and catalyst. Li et al 28 and Wang et al 29 revealed by means of the ab initio and DFT approaches, as well as experiments, that the catalytic activity on the surface of Pt metal to oxidation of methanol was attributed to formation of a stronger bond between Pt and hydrogen atoms in methanol molecule. As a result, CH 3 O • (or CH 3 O − ) was inevitably present on the surface of the electrode.…”
Section: H5077mentioning
confidence: 99%
“…One-dimensional metal–organic nanotubes (MONTs), a subgroup of 1D CPs, are promising molecular materials for potential applications in transport and separation, catalysis, and sensing. Chiral MONT aggregates are highly desirable for developing new functional materials that combine chirality and tube-related properties, but their synthesis remains a challenge . Most of the known chiral MONTs have a crystalline or hollow cylindrical morphology. ,, Chiral MONT assemblies with a macroscopic helical morphology are extremely rare.…”
Section: Introductionmentioning
confidence: 99%